Development of a Plywood-Based Wall Climbing Game to Enhance Cognitive Skills of 5–6-Year-Old Children - Irmayanti Devita Sari; Muhammad Yusuf; Leli Fertiliana Dea; Kholida Nur (Journal of Childhood Development, 2023)
This study aims to develop an instructional media in the form of a Wall Climbing game made from plywood to enhance cognitive abilities, particularly in problem-solving, among children aged 5–6 years at TK PKK Kotagajah. The research was motivated by preliminary findings indicating that the children’s cognitive development had not yet reached optimal levels despite ongoing classroom instruction. The method employed in this study is Research and Development (R&D), using the Borg and Gall model. Data were collected through observation, interviews, questionnaires, and documentation. The developed product emphasizes educational value, is tailored to the characteristics of early childhood learners, and is designed to be both safe and engaging. The results of the study demonstrate that the Wall Climbing game is effective in improving the cognitive abilities of children aged 5–6 years, particularly their problem-solving skills. This is evidenced by an increase in various cognitive indicators after using the learning media, such as exploratory behavior, application of prior knowledge in new contexts, and the ability to express creative ideas. The game also successfully fostered enthusiasm and motivation for learning throughout the instructional process. Therefore, the plywood-based Wall Climbing game can serve as an innovative and enjoyable alternative learning medium for promoting cognitive development in early childhood education